JENIS-JENIS PARASIT INTERNAL PADA FESES KAMBING (Capra sp.) DI PASAR KAMBING KOTA BENGKULU - Saputra, Hari Marta; Putra, Mahesha Rama Dwi (Universitas Bengkulu, 2019)
Parasitic diseases that are often a problem in livestock but are often ignored by farmers are intestinal worms caused by gastrointestinal worms. This study aims to determine the types of internal parasites in goat feces (Capra sp.). The study was conducted in July- August 2018 at the UPTD Laboratory and Animal Health Clinic in Bengkulu Province. Samples were taken from Bengkulu City Goat Market, then observed using native and sedimentation methods. The results of observing samples from three types of goat feces with negative methods obtained negative results, while observing samples by sedimentation method obtained six genus of worm eggs, specifically Ascaris sp., Ostertagia sp., Oesophagostomum sp., Strongyloides sp., Schistosoma sp., dan Skrjabinema sp.